FRI0073 First Report of Symptoms Using The Symptoms in Persons at Risk of Rheumatoid Arthritis (SPARRA) Questionnaire. (15th July 2016) - Beers-Tas, M.V.; Tuyl, L.V.; Raza, K.; Stack, R.; Finck, A.; Courvoisier, D.; Catrina, A.; Hensvold, A.; Mosor, E.; Stamm, T.; Schaardenburg, D.V.
Abstract : Background: Persons at risk of rheumatoid arthritis (RA) may experience a variety of symptoms 1, 2 . However, information on location, timing, severity and predictive value of these symptoms is largely lacking. The Symptoms in Persons At Risk of Rheumatoid Arthritis (SPARRA) questionnaire has been developed with support of EULAR to provide more insight into these symptoms. Objectives: Report the symptoms and symptom complexes using the SPARRA questionnaire in an international group of arthralgia patients at risk of developing RA. Methods: The SPARRA questionnaire contains questions on presence, severity, impact and location of 13 symptoms derived from a qualitative study in seropositive arthralgia patients 1 . The items are: joint pain or swelling, joint stiffness, burning and tingling sensations, numbness, changes in skin colour, muscle cramps, weakness, fatigue, emotional distress, concentration difficulties and sleep problems. Answers are given on an ordinal scale. If present, number of days with a symptom per month (0, 1–5, 6–15, 16–30 days), severity (none, mild, moderate and severe) and influence (no, small, moderate or high impact) were recorded. Secondly, we recorded the location of joint pain. Finally, patients were asked to describe the pattern of symptom development over time. Patients were included in the Netherlands (N=68), United Kingdom (N=16), Sweden (N=15), Austria (N=11) and Switzerland (N=21). Validation of the questionnaire is ongoing. Results: Of 131 arthralgia patients included, 85 were positive for anti-citrullinated protein antibodies (ACPA), 29 were positive for rheumatoid factor only, and 17 were seronegative with clinically suspect arthralgia. Most symptoms were present in a high percentage of patients, with pain as the most often experienced symptom and change of skin color rarely reported. When a symptom was present, it was usually experienced as moderate to severe, and with moderate impact by half of the patients (Table 1 ). The mean presence of symptoms was similar in the ACPA positive and negative groups, however, ACPA positive patients more often had severe symptoms (mean 61% versus 54%, NS) with higher impact (48% versus 41%, NS). Joint pain was most frequently located in the fingers. The most frequently reported pattern of symptoms was "coming and going, but always present" (32%). Conclusions: The first results of the SPARRA questionnaire show multiple symptoms to be present in a high percentage of persons at risk for RA. These are often experienced as severe, with a high impact. References: Stack, Rheumatology 2014; van Tuyl, Musculoskel Care 2015 Disclosure of Interest: None declared